Covenantal and dispensational theologies: four views on the continuity of scripture - Parker, Brent E.; Lucas, Richard James (Spectrum Multiview Book Ser., 2022)
How do the Old and New Testaments relate to each other? What is the relationship among the biblical covenants? In this volume in IVP Academic's Spectrum series, readers will find four contributors who explore these complex questions, each making a case for their own view and responding to the others' views to offer an animated yet irenic discussion on the continuity of Scripture.